Protein–Carbohydrate Complex Reveals Circulating Metastatic Cells in a Microfluidic Assay. Issue 12 (11th February 2013) - Simone, G.; Malara, N.; Trunzo, V.; Perozziello, G.; Neuzil, P.; Francardi, M.; Roveda, L.; Renne, M.; Prati, U.; Mollace, V.; Manz, A.; Di Fabrizio, E.
Abstract Advances in carbohydrate sequencing technologies reveal the tremendous complexity of the glycome and the role that glycomics might have to bring insight into the biological functions. Carbohydrate–protein interactions, in particular, are known to be crucial to most mammalian physiological processes as mediators of cell adhesion and metastasis, signal transducers, and organizers of protein interactions. An assay is developed here to mimic the multivalency of biological complexes that selectively and sensitively detect carbohydrate–protein interactions. The binding of β‐galactosides and galectin‐3—a protein that is correlated to the progress of tumor and metastasis—is examined. The efficiency of the assay is related to the expression of the receptor while anchoring to the interaction's strength. Comparative binding experiments reveal molecular binding preferences. This study establishes that the assay is robust to isolate metastatic cells from colon affected patients and paves the way to personalized medicine.